Kajian Kepuasan Pelanggan Terhadap Perkhidmatan ‘E-Hailing’ di Kuala Lumpur - Siti Norziah Ismail; Ameera Ainur Azman (Research in Management of Technology and Business, 2022)
"E-hailing’ is a process of ordering a car, taxi, limousine, or any other form of transportation pick up via a tablet or mobile device. With the ‘e- hailing’ apps, customer does not need to hail the empty taxi on the street, which may offer uncomfortable and inefficiency during the rush hours and raining day. The research aims to study the relationship between security feature, fare, payment method, ease of use, and satisfaction level on ‘e- hailing’ service in the Kuala Lumpur. The target sample in this study are ‘e- hailing’ users in the Kuala Lumpur. The sampling technique that is conducted in this study is non-probability sampling. The study approach will be used on 200 respondents who use ’e-hailing’. The study will be conducted with the aim of testing and analyzing whether there is a positive correlation between each independent variable including security features, cheaper fares, payment methods, and ease of use, and customer satisfaction as dependent variables. Data collected through questionnaires will be analyzed using Statistical Package for Social Science (SPSS) software. The results are expected to find that the results in identifying the relationship between independent variable factors influence customer satisfaction on ‘e-hailing’ in Kuala Lumpur